Acori Tatarinowii Rhizoma: A comprehensive review of its chemical composition, pharmacology, pharmacokinetics and toxicity - Wen, Jianxia; Yang, Yi; Hao, Junjie (Frontiers in Pharmacology, 2023)
Acori Tatarinowii Rhizoma (ATR, Shi Chang Pu in Chinese), a natural product with multiple targets in various diseases. This review provides the comprehensive summary of the chemical composition, pharmacological effects, pharmacokinetics parameters and toxicity of ATR. The results indicated that ATR possesses a wide spectrum of chemical composition, including volatile oil, terpenoids, organic acids, flavonoids, amino acids, lignin, carbohydrates and so on. Accumulating evidence from various studies has shown that ATR exerts a wide range of pharmacological properties, including protecting nerve cells, alleviating learning and memory impairment, anti-ischemic, anti-myocardial ischemia, anti-arrhythmic, anti-tumor, anti-bacterial, and anti-oxidant activities. Currently, ATR is widely used in the central nervous system, cardiovascular system, gastrointestinal digestive system, respiratory system in China, and for the treatment of epilepsy, depression, amnesia, consciousness, anxiety, insomnia, aphasia, tinnitus, cancers, dementia, stroke, skin diseases, and other complex diseases. Pharmacokinetic studies indicated that β-asarone, α-asarone, cis-methylisoeugenol, and asarylaldehyde, the active components of ATR, were absorbed slowly after oral administration of ATR. Moreover, toxicity studies have suggested that ATR has no carcinogenic, teratogenic and mutagenic toxicity. Nevertheless, long term or high-dose toxicity testing in animals to explore the acute and chronic toxicity of ATR is still lacking. In view of good pharmacological activities, ATR is expected to be a potential drug candidate for the treatment of Alzheimer's disease, depression, or ulcerative colitis. However, further studies are needed to elucidate its chemical composition, pharmacological effects, molecular mechanisms and targets, improve its oral bioavailability, and clarify its potential toxicity.